Anti-GBM of Pregnancy: Acute Renal Failure Resolved after Spontaneous Abortion, Plasma Exchange, Hemodialysis, and Steroids. (23rd June 2014) - Muqeet Adnan, Mohammed; Morton, Jordan; Hashmi, Syed; Abdul Mujeeb, Sufyan; Kern, William; Cowley, Benjamin Jr.
Abstract : Antiglomerular basement membrane disease presenting during pregnancy is very uncommon. We present a case of a pregnant female who presented with acute renal failure needing dialysis from Goodpasture's disease. She responded very well to just plasma exchange, high dose steroids, and hemodialysis. Cyclophosphamide was never started on this patient. She had a spontaneous abortion in her 8th week of pregnancy and henceforth did very well to regain her renal function. Patient became hemodialysis independent at 2 months and returned to her baseline kidney function at 6 months. We present this remarkable case of recovery from acute renal failure in a patient with anti-GBM disease. We think the flare-up of renal failure was pregnancy related which resolved after spontaneous abortion.